Change navigator : preparing a new kind of leader for an uncharted tomorrow - Hanks, Kurt (Crisp Pub. Menlo ParkUS, 1994)
Presents the adaptive leader as the change navigator whose task is to empower employees so that they can survive the changes and challenges of a very uncertain and unpredictable future, and be equipped with the tools to expand the opportunities that will be availabe to them. Explains how the adaptive leader can discern the mindset of his colleagues and utilise this knowledge in the process. Warns against misuse/abuse.